RNA lifetime control, from stereochemistry to gene expression. (April 2020) - Dendooven, Tom; Luisi, Ben F; Bandyra, Katarzyna J
Abstract : Through the activities of various multi-component assemblies, protein-coding transcripts can be chaperoned toward protein synthesis or nudged into a funnel of rapid destruction. The capacity of these machine-like assemblies to tune RNA lifetime underpins the harmony of gene expression in all cells. Some of the molecular machines that mediate transcript turnover also contribute to on-the-fly surveillance of aberrant mRNAs and non-coding RNAs. How these dynamic assemblies distinguish functional RNAs from those that must be degraded is an intriguing puzzle for understanding the regulation of gene expression and dysfunction associated with disease. Recent data illuminate what the machines look like, and how they find, recognise and operate on transcripts to sculpt the dynamic regulatory landscape. This review captures current structural and mechanistic insights into the key enzymes and their effector assemblies that contribute to the fate-determining decision points for RNA in post-transcriptional control of genetic information.